2018
DOI: 10.1002/cpt.1066
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Simulation Support Eltrombopag Dosing in Pediatric Patients With Immune Thrombocytopenia

Abstract: Our objective was to support initial eltrombopag doses and dose titration based on modeling and simulation of plasma exposure and platelet count response in pediatric patients aged 1-17 years with previously treated chronic immune thrombocytopenia enrolled in two clinical studies. Data from 168 pediatric patients were used to develop a life-span population pharmacokinetic and pharmacodynamic model including three pharmacokinetic and four pharmacodynamic compartments enabling simulation of platelet counts for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
2
16
2
Order By: Relevance
“…These may also contribute to a lower response rate to that observed in adults with CITP. Previous studies 10 have found a correlation between the efficacy of eltrombopag and its dosage, but this was not detected in our study. This discrepancy may be related to certain factors relevant to the children in our study, such as the underlying pathophysiology or the use of concomitant medication.…”
Section: Efficacycontrasting
confidence: 99%
“…These may also contribute to a lower response rate to that observed in adults with CITP. Previous studies 10 have found a correlation between the efficacy of eltrombopag and its dosage, but this was not detected in our study. This discrepancy may be related to certain factors relevant to the children in our study, such as the underlying pathophysiology or the use of concomitant medication.…”
Section: Efficacycontrasting
confidence: 99%
“…In this study, the median starting dose was 25 mg per day for children age 5 years or younger, 37.5 mg for children age 6 to 11 years, and 50 mg for children age 12 years or older. Owning to the differences in pharmacokinetics among races, 14 the FDA recommends a reduced initial dose of eltrombopag for patients with East Asian ancestry. However, even with the limited data in PETIT2, we can see that the average daily dose for East Asian children did not seem to be lower than that for the total cohort.…”
Section: Discussionmentioning
confidence: 99%
“…5,13 However, eltrombopag exhibited different metabolic properties among patients with Asian ancestry in the pharmacokinetics/pharmacodynamics model, resulting in relatively high exposure to the drug. 14 There are insufficient efficacy and safety data in PETIT2 to draw a suitable dosing recommendation for Asian children.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high relapse rates, the protocol was amended so that responders would continue CSA at a reduced dose (2 mg/kg daily) from 6 months to 2 years; the majority of the patients in the paediatric EPAG group were enrolled after this amendment ( n = 33, 83%) to receive CSA for 2 years. EPAG was dosed at 150 mg daily for patients aged ≥12 years, 75 mg for those aged 6–11 years and 2·5 mg/kg for those aged 2–5 years, with standard dosing adjustments made for patients of East Asian and Southeast Asian ancestry based on PK data in immune thrombocytopenic purpura 11 . The duration of EPAG administration was either 3 or 6 months, depending on assigned cohorts enrolled consecutively (Figure S1).…”
Section: Methodsmentioning
confidence: 99%
“…EPAG was dosed at 150 mg daily for patients aged ≥12 years, 75 mg for those aged 6-11 years and 2Á5 mg/kg for those aged 2-5 years, with standard dosing adjustments made for patients of East Asian and Southeast Asian ancestry based on PK data in immune thrombocytopenic purpura. 11 The duration of EPAG administration was either 3 or 6 months, depending on assigned cohorts enrolled consecutively ( Figure S1). Responders who relapsed were restarted on CSA and/or EPAG with a duration based on clinical response (Fig 1).…”
Section: Paediatric Epag Groupmentioning
confidence: 99%